Valuation of Malaysian timber companies. - Tan, Ee Swee. (2009)
Malaysian timber companies have attracted much attention recently due to the structural changes in the demand and supply patterns causing prices of timber goods to surge to record levels. A valuation of each company would involve various factors and variables, many of which are unique to the timber industry with the attending complication. A major factor arises from the global environmental movement concerned with the rapid destruction of tropical forest at current felling rate. Risks in valuation include changes in government policies and those arising from vertical integration. Valuation methods used such as the discounted cashflow, Capital Asset Pricing Model have limitations that need to be understood. Their use should be complemented by other approaches to aid in valuation and decision-making.